2005
DOI: 10.1099/mic.0.27476-0
|View full text |Cite
|
Sign up to set email alerts
|

The HiPIP from the acidophilic Acidithiobacillus ferrooxidans is correctly processed and translocated in Escherichia coli, in spite of the periplasm pH difference between these two micro-organisms

Abstract: The gene encoding a putative high-potential iron-sulfur protein (HiPIP) from the strictly acidophilic and chemolithoautotrophic Acidithiobacillus ferrooxidans ATCC 33020 has been cloned and sequenced. This potential HiPIP was overproduced in the periplasm of the neutrophile and heterotroph Escherichia coli. As shown by optical and EPR spectra and by electrochemical studies, the recombinant protein has all the biochemical properties of a HiPIP, indicating that the iron-sulfur cluster was correctly inserted. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 67 publications
7
40
0
Order By: Relevance
“…So, what role might Rpal_4085 play? There are examples of HiPIPs in nonphototrophic organisms that interact with the cytochrome bc 1 complex during respiration, such as those in Rhodothermus marinus (35,36) and Acidithiobacillus ferrooxidans (37,38). It is possible that Rpal_4085 serves a similar function in R. palustris respiration, although the ⌬Rpal_4085 mutant had no defect when growing aerobically on acetate and succinate under standard growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…So, what role might Rpal_4085 play? There are examples of HiPIPs in nonphototrophic organisms that interact with the cytochrome bc 1 complex during respiration, such as those in Rhodothermus marinus (35,36) and Acidithiobacillus ferrooxidans (37,38). It is possible that Rpal_4085 serves a similar function in R. palustris respiration, although the ⌬Rpal_4085 mutant had no defect when growing aerobically on acetate and succinate under standard growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3C). Substrate-dependent TatA-YFP association was also seen when an alternative Tat substrate, the Acidithiobacillus ferrooxidans high-potential iron-sulfur protein (HiPIP) (35), was overproduced and TatA association was again dependent on a functional signal peptide (Fig. 3 A-C).…”
Section: Coexpression With Tate Improves the Transport Activity Of Cellsmentioning
confidence: 93%
“…It has been found that the production of periplasmic redox holoproteins from the acidophilic A. ferrooxidans in neutrophilic E. coli has presented experimental problems. 35) Rusticyanin, a blue-copper protein, has been produced in the periplasm, but the copper was not incorporated and reconstitution in vitro was required. 36) No SQR activity was detected when the recombinant protein was reconstituted in the presence of FAD.…”
Section: Discussionmentioning
confidence: 99%